A hand-made supplementary food for malnourished children - Vanelli, Maurizio; Virdis, Raffaele; Contini, Sandro; Corradi, Mara; Cremonini, Giulia; Marchesi, Maddalena; Mele, Alessandra; Monti, Francesca; Pagano, Blandina; Proietti, Ilaria; Savina, Francesca; Verna, Marta; et al. (Acta Biomedica Atenei Parmensis, 2014)
We tested the possibility to prepare a hyperproteic and hyperenergetic supplementary food for malnutrition rehabilitation in children starting from available ingredients in popular markets in Sierra Leone. Twelve residents in Paediatrics from University of Parma, Italy, prepared in a hospital near the capital Freetown with modest technology a mixture of peanut flour, palm oil, milk powder, sugar and vitamins to which they gave the name of ”Parma pap”. Three hundred and thirty-two malnourished children (mean age 14±6.3 months) who were receiving Feeding Program Supplementations (FPS), were enrolled in the study: 177 participants received randomly FSP portions only (Group 1), and 159 participants were treated with FSP regimen plus a supplement of “Parma pap” (Group 2). Outcomes of the study were computed as WHZ-score increment (Δ value) by subtracting the discharge WHZ-score from the admission WHZ-score. The best Δ-WHZ-scores (>+4) were recorded among participants of Group 2 (64%) rather than in Group 1 (21%; p=0.040). The children receiving FSP portions plus “Parma pap” recovered faster (5.54 week on average) than those treated with FSP regimen only (8.16 on average). The percentage of children who did not recover was higher in Group 1 (25.3%) than in Group 2 (; 13%; p=0.05). A slight positive correlation has been found between WHZ-scores at admission and at the end of the study (r=0.19; p=0.045). During the experience in Sierra Leone we have had the chance to give “Parma pap” to twenty one malnourished children admitted to Xaverian Mission in Makeni, northern Sierra Leone, not taking other supplementary food. Sixteen of these children recovered in 4.9 week on average and five in 6 to 8 weeks. Mean Δ-WHZ-scores ranged between + 1 and + 5. The data from the present study suggest that “Parma pap” could be an effective additional food to FPS regimen in malnutrition recovering. Further researches are needed on the contrary to prove if “Parma pap” could be defined as a veritable ready to use therapeutic food, although this characteristic seems already to result from the experience in Makeni Mission.